Visible-Light-Mediated Synthesis of Trifluoromethylthiolated Arenes - Ghiazza, Clément; Monnereau, Cyrille; Khrouz, Lhoussain; Billard, Thierry; Tlili, Anis (Synthesis, 2019)
The visible-light-mediated synthesis of trifluoromethylthiolated arenes in the presence of ruthenium-based photocatayst under mild reaction conditions is reported. The trifluoromethylthiolated arenes are obtained using the shelf-stable reagent trifluoromethyl toluenethiosulfonate at room temperature. The reaction proceeds selectively and does not require the presence of any additive. A mechanism is proposed based on the obtained results of EPR as well as luminescence
Keywords: visible light; trifluoromethylthiolation; arenediazonium; radical; reaction mechanism